Impact of Emotional Intelligence on Organizational Performance in Commercial Banks, Itahari, Sunsari, Nepal - K.C., Pradeep (Journal of Janta Multiple Campus, 2024)
The ongoing debate surrounding Emotional Intelligence (EI) and Organizational Performance (OP) has been a consistent topic of discussion across various cultures worldwide. This article aims to assess the current status of EI and OP in Nepalese Commercial Banks, analyze the relationship between EI and OP, and measure the impact of EI on OP. Employing a deductive research approach, the study utilizes a descriptive and cross-sectional research design, with the population comprising all employees in commercial banks in Itahari, Sunsari, Nepal. The sample size is 167, chosen through convenience sampling, employing a structured questionnaire with a five-point Likert scale to collect primary data. Mean and Standard Deviations assess the status of EI and OP, while Pearson correlation matrix and linear regression analysis measure the impact of EI on OP. Chronbatch alpha is used to test the reliability of constructs. The results indicate a positive presentation of both EI and OP in commercial banks, with statistically significant relationships within the model. The analysis suggests that employees with high EI exhibit higher OP compared to those with lower emotional intelligence. Notably, social awareness emerges as a key construct significantly influencing OP, followed by relationship management and self-awareness. The findings propose potential benefits for banks in enhancing EI levels during recruitment, training, and development programs for their personnel.